DETERMINAN MAKROEKONOMI TERHADAP STOCK MARKET DEVELOPMENT DI ASEAN - Hazimah I’za Zain; Kim Sung Suk (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study investigates the relationship between macroeconomic factors and stock market development. Specifically, it examines the roles of gross domestic product, inflation, trade openness, financial intermediary development, investment rate, and saving rate across multiple dimensions of market development, including stock market capitalization, equity trading, turnover ratio, and the number of listed companies in ASEAN countries over the period 2000–2024. Testing methods conducted by a fixed effects panel data approach with Driscoll–Kraay standard errors to account for heteroscedasticity and cross-sectional dependence, the findings reveal substantial heterogeneity in the effects of macroeconomic variables. The results indicate that gross domestic product, inflation, financial intermediary development, and investment rate have an insignificant relationship across most stock market development indicators. Trade openness demonstrates a positive and significant relationship, particularly when proxied by equity trading and listed companies. Saving rate indicates a robust significant effect on stock market capitalization, further supported by turnover ratio dynamics. These findings highlight the differentiated transmission mechanisms of macroeconomic factors within ASEAN financial systems and underscore the need for coordinated macro-financial policies to enhance the complementarity between banking institutions and capital markets, thereby fostering sustainable market development.